Scrutinizing Integrative Learning in Arabic Instruction - Pradi Khusufi Syamsu; Achmad Satori Ismail; Sukron Kamil; Muhbib Abdul Wahab (International Journal of Islamic Thought and Humanities, 2023)
This research aims to find new ideas in integrative Arabic learning. The research conducted in this article is qualitative. Extracting research sources takes one form, sources of bibliographical data in the form of authoritative books and journal articles related to integrative Arabic learning. In terms of approach, this study uses a qualitative approach and a philosophical approach. The qualitative approach is related to the quality, value, or meaning that is explained through language or words. While the philosophical approach to explaining the scientific basis and nature or wisdom of a formal object. This study confirms that integrative Arabic learning is learning Arabic that combines the four language skills (listening, speaking, reading, and writing), elements of Arabic, language competence (competence linguistics, communicative competence, and cultural competence) and integrates all aspects of learning both academic and non-academic so that all Arabic learning programs are designed and implemented in an integrated and programmed manner in every student's daily life. Integrative Arabic learning is precisely in accordance with the character of the language itself which is an inseparable unit where the breadth of language must be treated as a whole and not narrowly. Several scholars who support the above opinion include Ibn Khaldun, Tamam Hassan, Ahmad Abduh Iwadh, Muhbib Abdul Wahab, Munther Younes, Farid Khalfawi, and Balqasim Malikiyah. The conclusion of this study is different from Noam Chomsky's opinion who concluded that language ability is a natural talent, not determined by the natural environment because language is not a habit.